2023
DOI: 10.3389/fpls.2023.1135552
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of DnaJ type-I protein homolog of Vigna aconitifolia (VaDJI) confers ABA insensitivity and multiple stress tolerance in transgenic tobacco plants

Abstract: Reduced crop productivity results from altered plant physiological processes caused by dysfunctional proteins due to environmental stressors. In this study, a novel DnaJ Type-I encoding gene, VaDJI having a zinc finger motif in its C-terminal domain was found to be induced early upon treatment with heat stress (within 5 min) in a heat tolerant genotype of Vigna aconitifolia RMO-40. VaDJI is induced by multiple stresses. In tobacco, ectopic expression of VaDJI reduced ABA sensitivity during seed germination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 102 publications
1
0
0
Order By: Relevance
“…This indicates that AdDjSKI may function downstream of this transcription factor in the ABA signal transduction pathway during seed germination. In accordance with our findings, previous findings have demonstrated that the constitutive expression of various genes, including WRKY20, GmbZIP62, OsPP108, and ABI5, imparts ABA insensitivity during seed germination and enhances tolerance to abiotic stresses, including drought and salinity (Brocard et al, 2002, Liao et al, 2008, Luo et al, 2013, Ahmed et al, 2018, Collin et al, 2020, Gautam et al, 2023. These findings underscore the significance of these genes in conferring multiple stress resistances and highlight their potential as targets for improving plant responses to environmental challenges.…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that AdDjSKI may function downstream of this transcription factor in the ABA signal transduction pathway during seed germination. In accordance with our findings, previous findings have demonstrated that the constitutive expression of various genes, including WRKY20, GmbZIP62, OsPP108, and ABI5, imparts ABA insensitivity during seed germination and enhances tolerance to abiotic stresses, including drought and salinity (Brocard et al, 2002, Liao et al, 2008, Luo et al, 2013, Ahmed et al, 2018, Collin et al, 2020, Gautam et al, 2023. These findings underscore the significance of these genes in conferring multiple stress resistances and highlight their potential as targets for improving plant responses to environmental challenges.…”
Section: Discussionsupporting
confidence: 92%